The Efficacy of Two‐Week Quadruple First‐Line Therapy with Bismuth, Lansoprazole, Amoxicillin, Clarithromycin on Helicobacter pylori Eradication: A Prospective Study. Issue 6 (9th September 2013) - Ergül, Bilal; Doğan,, Zeynal; Sarikaya, Murat; Filik, Levent
Abstract: Aim: To document the efficacy and tolerability of 14‐day bismuth–lansoprazole–amoxicillin–clarithromycin (BLAC) regimen for Helicobacter pylori ( H. pylori ) eradication as a first‐line therapy. Method: Patients were considered eligible for the study if they underwent upper gastrointestinal endoscopy, and H. pylori infection was diagnosed through histologic examination of antral and body biopsy samples. Primary end point of this study was to evaluate the eradication rate of 14‐day BLAC regimen therapies. H. pylori eradication was assessed using the 13C urea breath test performed 6 weeks after the completion of treatment. All patients were asked to fill in a validated questionnaire to report therapy‐related side effects. Each symptom was graded from absent or present. Results: Ninety‐seven (21 men and 76 women) were enrolled. All the patients completed the study. The H. pylori eradication rate was 90.7% (88 of 97 patients). Side effects were observed in reasonable percentages, and none of the patients left the study because of drug side effect. Conclusion: Bismuth–lansoprazole–amoxicillin–clarithromycin regimen as a 2‐week course achieved an acceptable eradication rate with relatively mild side effects.